Everybody needs good neighbours: understanding the conflict(s) in Eastern DRC - Johan Pottier (Cadernos de Estudos Africanos)
Widely recognized as Africa's most complex war, even dubbed Africa's First World War, the current conflict in the Democratic Republic of Congo «Stems from the wave of violence and mass-displacement unleashed by the Rwandan genocide in 1994» (APPG 2001: 6). This paper outlines the broad contours of the DRC conflict(s) in international, national and local terms. In particular, it aims to provide a full context to the Inter-Congolese Dialogue (Sun City, South Africa, on 25 February 2002) by exploring the overlapping «local» contexts in which tensions arise. Focusing on Eastern DRC, the paper also highlights the ever-shifting nature of alliances, and reflects on the challenges that need to be confronted if peace is to be given a chance.